Chemical constituents from Bupleurum chinese and their chemotaxonomic significance. (October 2019) - Li, Danqi; Yue, Dandan; Liu, Da; Liu, Xuegui; Song, Shaojiang
Abstract: A phytochemical investigation of the roots of Bupleurum chinese DC. led to the isolation of eighteen compounds, including three chromones (1 –3 ), seven flavonoids (4 –10 ), one dihydrochalcone (11 ), two phenylpropanoid glycosides (12–13 ), one lignan (14 ), three sterols (15 –17 ) and one stilbenoid (18 ). Their structures were elucidated on the basis of NMR spectroscopic analysis and comparison with literature data. Compounds6–7, 11–14 and18 were firstly reported from the genus Bupleurum and the family Apiaceae. Moreover, the chemotaxonomic value of the isolates was also discussed. Highlights: The phytochemical investigation of Bupleurum chinese DC. resulted in 18 compounds. Compounds 6–7, 11–14, 18 were reported from the genus Bupleurum and family Apiaceae for the first time. Compounds 6–7, 11–14, 18 could serve as potential chemotaxonomic markers to identify B. chinense.